Research on the application of Chinese style illustration in traditional food packaging design - YAN Mengjie; ZHANG Jian (Shipin yu jixie, 2024)
As a unique visual expression of China, Chinese style illustration considers both connotation and artistry. This paper analyzes the artistic expression of Chinese style illustration and its application value in traditional food packaging design. It is found that the application of Chinese style illustration in traditional food packaging design can create a differentiated brand image, enhance the communication of brand culture, and establish brand loyalty among consumers. The application strategy of national style illustration in traditional food packaging design is also proposed.